PSMA-Specific CAR-Engineered T Cells for Prostate Cancer: CD28 Outperforms Combined CD28-4-1BB “Super-Stimulation” - Zuccolotto, Gaia; Penna, Alessandro; Fracasso, Giulio; Carpanese, Debora; Montagner, Isabella Monia; Dalla Santa, Silvia; Rosato, Antonio (Frontiers in Oncology, 2021)
Prostate cancer (PCa) is the second leading cause of malignancy-related mortality in males in the Western world. Although treatment like prostatectomy and radiotherapy for localized cancer have good results, similar positive outcomes are not achieved in metastatic PCa. Consequently, these aggressive and metastatic forms of PCa urgently need new methods of treatment. We already described an efficient and specific second-generation (2G) Chimeric Antigen Receptor (CAR) against Prostate Specific Membrane Antigen (PSMA), a glycoprotein overexpressed in prostate cancer and also present on neovasculature of several tumor entities. In an attempt to improve efficacy and in vivo survival of anti-PSMA 2G CAR-T cells, we developed a third generation (3G) CAR containing two costimulatory elements, namely CD28 and 4-1BB co-signaling domains, in addition to CD3ζ. Differently from what described for other 3G receptors, our third generation CAR disclosed an antitumor activity in vitro similar to the related 2G CAR that comprises the CD28 co-signaling domain only. Moreover, the additional costimulatory domain produced detrimental effects, which could be attributed to an increased activation-induced cell death (AICD). Indeed, such “superstimulation” resulted in an exhausted phenotype of CAR-T cells, after prolonged in vitro restimulation, a higher frequency of cell death, and an impairment in yielding sufficient numbers of transgenic T lymphocytes. Thus, the optimal combination of costimulatory domains for CAR development should be assessed cautiously and evaluated case-by-case.